Home based rehabilitation versus supervised physiotherapy based rehabilitation for first 6 months post Anterior Cruciate Ligament (ACL) reconstruction in recreational athletes - Zain, Muhammad Rajaei Ahmad@Mohd (2018)
Background: Home-based rehabilitation is an alternative method of physiotherapy after anterior cruciate ligament (ACL) reconstruction to regain pre injury state level. We conducted a prospective interventional study to investigate the outcome of a newly modified home-based (HB) physiotherapy program for patient post (ACL) reconstruction as comparison with supervised physiotherapy (SP) within 6 months that would be a cost effective and toward patient-directed rehabilitation to improve compliance. Objective: The aim for this study was to compare the outcome of post ACL reconstruction rehabilitation between a complete HB rehabilitation and the conventional SP rehabilitation program. Methodology: This was a prospective interventional study conducted over 1 year. There were 34 patients with ACL injury randomized either into a HB or SP program. Twenty seven patients successfully completed rehabilitation based on a standard regime of exercises. 15 of them were in the SP group while 12 were in the HB group. Patients were given an explanation, an instructional video CD and equipment to perform the HB rehabilitation. All patients were reviewed at 6 weeks, 3 months and 6 months post ACL reconstruction for evaluation. Knee motion, muscle strength and power, knee stability, and functional outcomes were assessed to investigate the comparison between both groups. Results: The mean age for both groups was almost similar; 24.4 in the HB group and 25 in the SP group. 20 of the 27 patients were male. There was an excellent result of range of motion in the HB group as all patients achieved the targeted goal, however, 1 patient did not achieve the targeted range of motion in the early phase for the SP group. Functional outcome scores improved at 6 months as comparison score at 3 months for both groups with mean scores from 86 to 97 and 84 to 95 respectively, but statistically insignificant between both groups (P value 0.652 at 3 month and 0.323 at 6 month). Knee laxity using KT 1000 did not show any significant difference at 6 months (p: 0.371). Both quadriceps and hamstrings muscle strengths that were measured at 2 different speeds (180° and 300° per second) showed no significant difference as well as knee power after 6 months home-based physiotherapy. Conclusion: Home-based rehabilitation was as effective as supervised physiotherapy in terms of functional outcome scores, knee range of motion, knee laxity, and muscle strength and knee power for the first 6 months after ACL reconstruction surgery.